Movement plans for posture selection do not transfer across hands - Schütz, Christoph; Schack, Thomas (Frontiers in Psychology, 2015)
In a sequential task, the grasp postures people select depend on their movement history. This motor hysteresis effect results from the reuse of former movement plans and reduces the cognitive cost of movement planning. Movement plans for hand trajectories not only transfer across successive trials, but also across hands. We therefore asked whether such a transfer would also be found in movement plans for hand postures. To this end, we designed a sequential, continuous posture selection task. Participants had to open a column of drawers with cylindrical knobs in ascending and descending sequences. A hand switch was required in each sequence. Hand pro/supination was analyzed directly before and after the hand switch. Results showed that hysteresis effects were present directly before, but absent directly after the hand switch. This indicates that, in the current study, movement plans for hand postures only transfer across trials, but not across hands.